A method for preparing porous polyaniline / polylactic acid conductive fiber
By soaking the polyaniline/polylactic acid nanofiber membrane prepared by electrospinning in a volatile acetone/ethanol blend solvent, the problem of difficulty in forming a porous structure inside the fibers in the prior art is solved, and the preparation of the porous structure is achieved, and the residue of excess components is removed.
Patent Information
- Application Number
- CN202310490735.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-04
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-05-04
AI Technical Summary
In the prior art, when preparing porous fibers, it is difficult to form a porous structure inside the fibers and it is difficult to remove excess components.
The polyaniline/polylactic acid nanofiber membrane prepared by electrospinning was immersed in a volatile acetone/ethanol blend solvent, and the porous structure was formed by volatilization of the solvent, and the solvent was removed by simple treatment.
The formation of a porous structure inside the fiber is achieved, and the preparation method is simple and convenient, without any residual components.
Smart Images

Figure CN116516520B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of conductive fibers, and more specifically to a method for preparing porous polyaniline / polylactic acid conductive fibers. Background Art
[0002] At present, there are generally two methods for preparing porous fibers by electrospinning. The first is that during the electrospinning process, the phase separation of the polymer solution is caused by solvents, temperature differences, etc., resulting in pores. In this case, pores can generally only be formed on the surface of the fiber. The second is to selectively dissolve the components in the electrospun fiber to obtain a porous structure. This method requires a reasonable selection of the blend and post-processing solvent, and it is difficult to completely remove the added components. Summary of the invention
[0003] In view of the problems existing in the background technology, the purpose of the present invention is to provide a method for preparing porous polyaniline / polylactic acid conductive fibers, which utilizes solvent to soak the fibers to form pores and removes the solvent by simple volatilization. The preparation method is simple and convenient, and no excess components remain.
[0004] In order to achieve the above-mentioned object, the present invention provides a method for preparing porous polyaniline / polylactic acid conductive fibers, comprising the following steps: (1) preparing polyaniline / polylactic acid nanofibers: grinding and mixing polyaniline and camphorsulfonic acid in a ratio of 0.8 / 1-1.2 / 1, then dissolving the ground sample in a hexafluoroisopropanol solvent to prepare a 10-20 mg / mL solution, stirring thoroughly and filtering using a polytetrafluoroethylene filter membrane with a pore size of 0.22-0.45 μm, adding polylactic acid in a ratio of 80-120 mg / mL to the filtered polyaniline / camphorsulfonic acid / hexafluoroisopropanol solution and stirring thoroughly, electrospinning the above precursor solution to obtain a conductive polyaniline / polylactic acid nanofiber membrane; (2) preparing a porous structure of polyaniline / polylactic acid fibers: immersing the polyaniline / polylactic acid nanofiber membrane prepared by electrospinning in an acetone / ethanol blended solvent to obtain a porous structure of polyaniline / polylactic acid nanofibers.
[0005] Optionally, in step (1), during the electrospinning process, the electrospinning voltage is 15-25 kV, the sample introduction rate is 0.2-1.0 mL / h, the spinning receiving distance is 10-20 cm, and the receiving roller speed is 200-1000 r / min.
[0006] Optionally, in step (1), polyaniline and camphorsulfonic acid are ground and mixed in a ratio of 1:1, and then the ground sample is dissolved in a hexafluoroisopropanol solvent to prepare a 15 mg / mL solution, and after sufficient stirring, it is filtered using a polytetrafluoroethylene filter membrane with a pore size of 0.22 μm, and polylactic acid is added to the filtered polyaniline / camphorsulfonic acid / hexafluoroisopropanol solution at a rate of 80 mg / mL and fully stirred, and the above precursor solution is electrospun to obtain a conductive polyaniline / polylactic acid nanofiber membrane.
[0007] Optionally, in step (1), during the electrospinning process, the electrospinning voltage is 20 kV, the sample feed rate is 0.5 mL / h, the spinning receiving distance is 15 cm, and the receiving roller speed is 300 r / min to obtain a conductive polyaniline / polylactic acid nanofiber membrane.
[0008] Optionally, in step (2), the polyaniline / polylactic acid nanofiber membrane prepared by electrospinning is immersed in an acetone / ethanol blended solvent at a temperature of -18°C to 15°C for at least 0.5 h, and the blending volume ratio of the acetone / ethanol blended solvent is 4 / 1 to 1 / 1.
[0009] Optionally, in step (2), the polyaniline / polylactic acid nanofiber membrane prepared by electrospinning is immersed in an acetone / ethanol blended solvent at a temperature of 5° C. for 1 h, and the blending volume ratio of the acetone / ethanol blended solvent is 3 / 1-2 / 1.
[0010] Optionally, in step (2), the blending volume ratio of acetone / ethanol blending solvent is 2 / 1.
[0011] Optionally, in step (2), the blending volume ratio of acetone / ethanol blending solvent is 3 / 1.
[0012] Optionally, the conductivity of the prepared porous polyaniline / polylactic acid conductive fiber is 1*10 -4 -1*10 -6 S / cm.
[0013] Optionally, the prepared porous polyaniline / polylactic acid conductive fiber is used as a catalyst carrier or for preparing a flexible pressure sensor.
[0014] The beneficial effects of the present invention are as follows:
[0015] 1. The present invention utilizes volatile solvents to soak fibers to form pores, and the solvent can be removed by simple solvent volatilization. The preparation method is simple and convenient, and no redundant components remain.
[0016] 2. The present invention can adjust the porosity of the polyaniline / polylactic acid fiber by selecting acetone / ethanol blended solvents of different volume ratios for immersion.
[0017] Further features and advantages of the present invention will become apparent from the following detailed description of exemplary embodiments of the present invention with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The test results of the scanning electron microscope test of the samples obtained in Comparative Example 1, Example 1, Example 2, and Comparative Example 2 are shown in FIG. 1 , wherein the scanning electron microscope images of Comparative Example 1, Example 1, Example 2, and Comparative Example 2 are respectively Figure 1 (a) Figure 1 (b) Figure 1 (c) and Figure 1 (d).
[0019] Figure 2 The test results of the scanning electron microscope test of the samples obtained in Comparative Example 4, Comparative Example 3, and Comparative Example 5 are as follows: Figure 2 (a) Figure 2 (b) Figure 2 (c).
[0020] Figure 3 These are the test results of XRD tests on the samples obtained in Comparative Example 6, Comparative Example 7, and Example 2.
[0021] Figure 4 The test results of the scanning electron microscope test of the samples obtained in Example 2 and Comparative Example 8 are as follows, wherein the scanning electron microscope images of Example 2 and Comparative Example 8 are respectively Figure 4 (a) Figure 4 (b). DETAILED DESCRIPTION
[0022] In order to make the above-mentioned objects, features and advantages of the invention more obvious and easy to understand, the specific embodiments of the invention are described in detail below.
[0023] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0024] The method for preparing porous polyaniline / polylactic acid conductive fibers according to the present invention comprises the following steps:
[0025] (1) Preparation of polyaniline / polylactic acid nanofibers: polyaniline and camphorsulfonic acid are ground and mixed in a ratio of 0.8 / 1-1.2 / 1, and then the ground sample is dissolved in a hexafluoroisopropanol solvent to prepare a 10-20 mg / mL solution, and after sufficient stirring, it is filtered using a polytetrafluoroethylene filter membrane with a pore size of 0.22-0.45 μm, and polylactic acid is added to the filtered polyaniline / camphorsulfonic acid / hexafluoroisopropanol solution at a rate of 80-120 mg / mL and fully stirred, and the above precursor solution is electrospun to obtain a conductive polyaniline / polylactic acid nanofiber membrane; (2) Preparation of a porous structure of polyaniline / polylactic acid fibers: The polyaniline / polylactic acid nanofiber membrane prepared by electrospinning is immersed in an acetone / ethanol blended solvent to obtain a porous structure of polyaniline / polylactic acid nanofibers. Wherein, sufficient stirring means that the mixed solution is stirred evenly, and the time can be 2-6 hours.
[0026] In one embodiment of the present invention, in step (1), during the electrospinning process, the electrospinning voltage is 15-25 kV, the feed rate is 0.2-1.0 mL / h, the spinning receiving distance is 10-20 cm, and the receiving roller speed is 200-1000 r / min.
[0027] In one embodiment of the present invention, in step (2), the polyaniline / polylactic acid nanofiber membrane prepared by electrospinning is immersed in an acetone / ethanol blended solvent at a temperature of -18°C to 15°C, for a time of at least 0.5 h, and the blending volume ratio of the acetone / ethanol blended solvent is 4 / 1 to 1 / 1.
[0028] In a preferred embodiment of the present invention, in step (1), polyaniline and camphorsulfonic acid are ground and mixed in a ratio of 1:1, and then the ground sample is dissolved in a hexafluoroisopropanol solvent to prepare a 15 mg / mL solution, and after sufficient stirring, it is filtered using a polytetrafluoroethylene filter membrane with a pore size of 0.22 μm, and polylactic acid is added to the filtered polyaniline / camphorsulfonic acid / hexafluoroisopropanol solution at a rate of 80 mg / mL and fully stirred, and the above precursor solution is electrospun to obtain a conductive polyaniline / polylactic acid nanofiber membrane.
[0029] In a preferred embodiment of the present invention, in step (1), during the electrospinning process, the electrospinning voltage is 20 kV, the feed rate is 0.5 mL / h, the spinning receiving distance is 15 cm, and the receiving roller speed is 300 r / min to obtain a conductive polyaniline / polylactic acid nanofiber membrane.
[0030] In a preferred embodiment of the present invention, the polyaniline / polylactic acid nanofiber membrane prepared by electrospinning is immersed in an acetone / ethanol blended solvent, the immersion temperature is 5°C, the immersion time is 1h, and the blending volume ratio of the acetone / ethanol blended solvent is 3 / 1-2 / 1. In one embodiment, the blending volume ratio of the acetone / ethanol blended solvent is 2 / 1. In another embodiment, the blending volume ratio of the acetone / ethanol blended solvent is 3 / 1. In the electrospinning process of the present invention, the spinning solvent evaporates rapidly, and the prepared polylactic acid fiber is amorphous. When immersed in an acetone / ethanol blended solvent, polylactic acid and acetone / ethanol have similar solubility parameters. The solvent can penetrate and swell the polylactic acid, improve the fluidity of the molecular chain, and cause a large amount of crystallization of the polylactic acid (refer to Figure 3 ), resulting in phase separation. When the acetone / ethanol solvent evaporates, a porous structure is formed. The porosity of the polyaniline / polylactic acid fiber can be controlled by controlling the blending volume ratio of acetone / ethanol and the soaking temperature.
[0031] The conductivity of the porous polyaniline / polylactic acid conductive fiber prepared according to the present invention is 1*10 -4 -1*10 -6 In one embodiment, the conductivity of the porous polyaniline / polylactic acid conductive fiber is 6.2*10 -5 -7.6*10 -5 The porous polyaniline / polylactic acid conductive fiber prepared according to the present invention can be used as a catalyst carrier or for preparing a flexible pressure sensor.
[0032] The method for preparing porous polyaniline / polylactic acid conductive fibers of the present invention is described in detail below in conjunction with specific examples.
[0033] Example 1
[0034] Step (1) preparing polyaniline / polylactic acid nanofibers: grinding and mixing polyaniline and camphorsulfonic acid in a ratio of 1:1, then dissolving the ground sample in a hexafluoroisopropanol solvent to prepare a 15 mg / mL solution, stirring for 4 hours, and filtering using a polytetrafluoroethylene filter membrane with a pore size of 0.22 μm, adding polylactic acid at 80 mg / mL to the filtered polyaniline / camphorsulfonic acid / hexafluoroisopropanol solution, and stirring for 12 hours, electrospinning the above precursor solution, the electrospinning voltage is 20 kV, the sample feed rate is 0.5 mL / h, the spinning receiving distance is 15 cm, and the receiving drum speed is 300 r / min, to obtain a conductive polyaniline / polylactic acid nanofiber membrane.
[0035] Step (2) Preparation of a porous structure of polyaniline / polylactic acid fibers: soaking the polyaniline / polylactic acid nanofiber membrane prepared by electrospinning in an acetone / ethanol blended solvent at a temperature of 5° C. for 1 h, and a blending volume ratio of the acetone / ethanol blended solvent of 2 / 1.
[0036] Example 2
[0037] The difference from Example 1 is that the blending volume ratio of the acetone / ethanol blended solvent is 3 / 1.
[0038] Comparative Example 1
[0039] The difference from Example 1 is that the blending volume ratio of acetone / ethanol blended solvent is 0 / 1.
[0040] Comparative Example 2
[0041] The difference from Example 1 is that the blending volume ratio of acetone / ethanol blended solvent is 1 / 0.
[0042] Comparative Example 3
[0043] The difference from Example 1 is that the soaking temperature is 25°C.
[0044] Comparative Example 4
[0045] The difference from Example 2 is that the soaking temperature is 25°C.
[0046] Comparative Example 5
[0047] The difference from Example 1 is that the immersion temperature is 25° C., and the blending volume ratio of the acetone / ethanol blending solvent is 3 / 2.
[0048] Comparative Example 6
[0049] The polyaniline / polylactic acid fiber membrane prepared by step (1) of Example 1.
[0050] Comparative Example 7
[0051] The polyaniline / polylactic acid fiber membrane prepared by step (1) of Example 1 was cold crystallized at 75° C. for 3 h.
[0052] Comparative Example 8
[0053] The polyaniline / polylactic acid fiber prepared in step (1) of Example 1 was cold crystallized at 90° C. for 2 h, and then immersed in an acetone / ethanol blend solvent with a blend volume ratio of 3 / 1 at 5° C. for 1 h.
[0054] Performance Testing and Results
[0055] 1. The samples obtained in Example 1 and Example 2 were tested for conductivity using the four-probe method. The conductivity of the sample in Example 1 was 7.6*10 -5 S / cm, the conductivity of the sample in Example 2 is 6.2*10 -5 S / cm.
[0056] 2. The samples obtained from Comparative Example 1, Example 1, Example 2, and Comparative Example 2 were tested by scanning electron microscope. The test results are as follows: Figure 1 As shown, the scanning electron microscope images of Comparative Example 1, Example 1, Example 2, and Comparative Example 2 are respectively Figure 1 (a) Figure 1 (b) Figure 1 (c) and Figure 1 (d).
[0057] Figure 1 The scanning electron microscope images of each sample obtained after the polyaniline / polylactic acid fiber membrane was immersed in acetone / ethanol blended solvents with different blending volume ratios at 5°C for 1 hour, wherein: Figure 1 (a) Figure 1 (b) Figure 1 (c) and Figure 1 The blending volume ratios of acetone / ethanol in (d) are 0 / 1, 2 / 1, 3 / 1, and 1 / 0, respectively. Figure 1 As shown in (a), when the polyaniline / polylactic acid fiber membrane is immersed in pure ethanol solvent, the fiber diameter becomes larger, but no pore structure appears. When the polyaniline / polylactic acid fiber membrane is immersed in acetone / ethanol blended solvents with a blending volume ratio of 2 / 1 and 3 / 1, the fiber morphology can be maintained, and the fiber porosity increases with the increase of acetone content, as shown in Figure 1 (b) Figure 1 (c) When the polyaniline / polylactic acid fiber membrane is immersed in pure acetone solvent, a large number of pore structures can be formed, but the morphology of the fiber is destroyed, as shown in Figure 1 (d) as shown.
[0058] Experiments have found that the pore formation of polyaniline / polylactic acid fibers is closely related to the solubility parameter of the selected solvent. It is known that the solubility parameter of chloroform is 9.3 cal 1 / 2 * cm -3 / 2 Since polylactic acid fiber can be completely dissolved in chloroform solvent, it is inferred that the solubility parameter of polylactic acid is approximately 9.3 cal 1 / 2 * cm -3 / 2 The solubility parameter of acetone is 9.8 cal 1 / 2 * cm-3 / 2 , the solubility parameter of ethanol is 12.9 cal 1 / 2 * cm -3 / 2 . The solubility parameter of acetone is similar to that of polylactic acid, so acetone can swell polylactic acid, but it cannot completely dissolve polylactic acid. During the swelling process, the mobility of the polylactic acid molecular chain can be improved, inducing its crystallization, resulting in phase separation of polylactic acid and solvent, and forming a porous structure after the solvent evaporates, but the swelling effect of acetone is too strong, which will destroy the fiber structure of polyaniline / polylactic acid. The solubility parameter of ethanol is quite different from that of polylactic acid, and its swelling effect on polylactic acid is lower than that of acetone, and it cannot induce the formation of a porous structure. By blending acetone / ethanol, the solubility parameter of the solvent can be adjusted, and the swelling effect of the solvent on polylactic acid can be controlled. When forming a porous structure, the structure of the fiber is ensured not to be destroyed, and a porous fiber structure is obtained. And with the increase of the volume ratio of acetone / ethanol, the swelling effect of the solvent on the fiber membrane is enhanced, the mobility of the polylactic acid molecular chain is improved, the crystallinity is increased, and the phase separation phenomenon is more obvious, resulting in an increase in porosity.
[0059] 3. The samples obtained in Comparative Examples 4, 3 and 5 were subjected to scanning electron microscope tests. The test results are as follows: Figure 2 As shown, the scanning electron microscope images of Comparative Example 4, Comparative Example 3, and Comparative Example 5 are respectively Figure 2 (a) Figure 2 (b) Figure 2 (c).
[0060] Figure 2 The scanning electron microscope images of each sample obtained after the polyaniline / polylactic acid fiber membrane was immersed in acetone / ethanol blended solvents with different blending volume ratios at 25°C for 1 hour. Among them, Figure 2 (a) Figure 2 (b) and Figure 2 The blending volume ratios of acetone / ethanol in (c) are 3 / 1, 2 / 1, and 3 / 2, respectively. At 25°C, polyaniline / polylactic acid fibers can form a porous structure, but the fiber structure is destroyed, and the degree of fiber structure destruction increases with the increase of acetone content. Figure 1 (b) Figure 1 The comparison of the test results of (c) shows that temperature affects the preparation of polyaniline / polylactic acid porous fibers. As the solvent treatment temperature increases, the mobility of the polylactic acid molecular chain increases, and the fiber structure is more easily destroyed.
[0061] 4. The samples obtained in Comparative Example 6, Comparative Example 7 and Example 2 were subjected to XRD test. The test results are as follows: Figure 3 shown.
[0062] Depend on Figure 3From the XRD diagram, it can be seen that the polyaniline / polylactic acid fiber prepared by electrospinning has no diffraction peak, so the polyaniline / polylactic acid electrospun fiber is amorphous. After the polyaniline / polylactic acid fiber is cold crystallized at 75℃ for 3h, the (200) / (110) crystal diffraction peak of polylactic acid can be seen. After the polyaniline / polylactic acid fiber is immersed in an acetone / ethanol solvent with a blending volume ratio of 3 / 1 for 1h, it has sharp (200) / (110), (203), and (210) polylactic acid crystal diffraction peaks, which proves that the polylactic acid in the polyaniline / polylactic acid fiber is largely crystallized. During the electrospinning process, the solvent evaporates quickly, and the prepared polylactic acid fiber is amorphous. When immersed in acetone / ethanol solvent, polylactic acid has similar solubility parameters to acetone / ethanol solvent. The solvent can penetrate and swell polylactic acid, improve the fluidity of the molecular chain, and cause a large amount of crystallization of polylactic acid, resulting in phase separation. When the acetone / ethanol solvent evaporates, a porous structure is formed.
[0063] 5. The samples obtained in Example 2 and Comparative Example 8 were tested by scanning electron microscope. The test results are as follows: Figure 4 As shown, the scanning electron microscope images of Example 2 and Comparative Example 8 are respectively Figure 4 (a) Figure 4 (b).
[0064] Figure 4 (a) is a scanning electron micrograph of a polyaniline / polylactic acid fiber membrane directly immersed in an acetone / ethanol blend solvent with a blend volume ratio of 3 / 1 at 5°C for 1 hour. Figure 4 In (a), it can be observed that a large number of pore structures are formed in the polyaniline / polylactic acid fibers. Figure 4 (b) is a scanning electron microscope image of the polyaniline / polylactic acid fiber membrane after cold crystallization at 90°C for 2 hours and then in an acetone / ethanol blend solvent at 5°C with a blend volume ratio of 3 / 1 for 1 hour. At this time, the polyaniline / polylactic acid fiber did not form a porous structure. The difference in the morphology of the polyaniline / polylactic acid fiber before and after crystallization further proves that the porous structure of the polyaniline / polylactic acid fiber is induced by crystallization.
[0065] Although some specific embodiments of the present invention have been described in detail by way of example, it will be appreciated by those skilled in the art that the above examples are for illustration only and are not intended to limit the scope of the present invention. It will be appreciated by those skilled in the art that the above embodiments may be modified without departing from the scope and spirit of the present invention. The scope of the present invention is defined by the appended claims.
Claims
1. A method for preparing porous polyaniline / polylactic acid conductive fibers, characterized in that: The following steps are involved: (1) Preparation of polyaniline / polylactic acid nanofibers: polyaniline and camphorsulfonic acid are ground and mixed in a ratio of 0.8 / 1-1.2 / 1, and then the ground sample is dissolved in a hexafluoroisopropanol solvent to prepare a 10-20 mg / mL solution, and after sufficient stirring, it is filtered using a polytetrafluoroethylene filter membrane with a pore size of 0.22-0.45 μm, and polylactic acid is added to the filtered polyaniline / camphorsulfonic acid / hexafluoroisopropanol solution at a rate of 80-120 mg / mL and fully stirred, and the above precursor solution is electrospun to obtain a conductive polyaniline / polylactic acid nanofiber membrane; (2) Preparing a porous structure of polyaniline / polylactic acid fibers: soaking the polyaniline / polylactic acid nanofiber membrane prepared by electrospinning in an acetone / ethanol blended solvent to obtain a porous structure of polyaniline / polylactic acid nanofibers; In step (2), the polyaniline / polylactic acid nanofiber membrane prepared by electrospinning is immersed in an acetone / ethanol blended solvent at a temperature of -18°C to 15°C for at least 0.5 h, and the blending volume ratio of the acetone / ethanol blended solvent is 4 / 1 to 1 / 1.
2. The method for preparing porous polyaniline / polylactic acid conductive fibers according to claim 1, characterized in that: In step (1), during the electrospinning process, the electrospinning voltage is 15-25 kV, the sample introduction rate is 0.2-1.0 mL / h, the spinning receiving distance is 10-20 cm, and the receiving roller speed is 200-1000 r / min.
3. The method for preparing porous polyaniline / polylactic acid conductive fiber according to claim 1, characterized in that: In step (1), polyaniline and camphorsulfonic acid are ground and mixed in a ratio of 1:1, and then the ground sample is dissolved in a hexafluoroisopropanol solvent to prepare a 15 mg / mL solution, and after sufficient stirring, it is filtered using a polytetrafluoroethylene filter membrane with a pore size of 0.22 μm. In the filtered polyaniline / camphorsulfonic acid / hexafluoroisopropanol solution, polylactic acid is added at 80 mg / mL and fully stirred, and the above precursor solution is electrospun to obtain a conductive polyaniline / polylactic acid nanofiber membrane.
4. The method for preparing porous polyaniline / polylactic acid conductive fiber according to claim 2, characterized in that: In step (1), during the electrospinning process, the electrospinning voltage is 20 kV, the sample feed rate is 0.5 mL / h, the spinning receiving distance is 15 cm, and the receiving roller speed is 300 r / min, thereby obtaining a conductive polyaniline / polylactic acid nanofiber membrane.
5. The method for preparing porous polyaniline / polylactic acid conductive fiber according to claim 1, characterized in that: In step (2), the polyaniline / polylactic acid nanofiber membrane prepared by electrospinning is immersed in an acetone / ethanol blended solvent at a temperature of 5° C. for 1 h. The blending volume ratio of the acetone / ethanol blended solvent is 3 / 1-2 / 1.
6. The method for preparing porous polyaniline / polylactic acid conductive fibers according to claim 5, characterized in that: In step (2), the blending volume ratio of acetone / ethanol blending solvent is 2 / 1.
7. The method for preparing porous polyaniline / polylactic acid conductive fibers according to claim 5, characterized in that: In step (2), the blending volume ratio of acetone / ethanol blending solvent is 3 / 1.
8. The method for preparing porous polyaniline / polylactic acid conductive fiber according to claim 1, characterized in that: The conductivity of the prepared porous polyaniline / polylactic acid conductive fiber is 1*10 -4 -1*10 -6 S / cm.
9. The method for preparing porous polyaniline / polylactic acid conductive fibers according to claim 1, characterized in that: The prepared porous polyaniline / polylactic acid conductive fiber is used as a catalyst carrier or for preparing a flexible pressure sensor.
Citation Information
Patent Citations
Method for preparing polymer porous nanofiber through mixed phase separation
CN102517673A
Preparation method of polylactic acid / polyaniline composite conductive fiber
CN103243563A